2018
DOI: 10.1186/s12889-018-5143-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological factors in predicting latrine ownership and consistent latrine use in rural Ethiopia: a cross-sectional study

Abstract: BackgroundInadequate sanitation is one of the leading causes of disease in poor and middle-income countries.ObjectiveThe objective of the study was to identify the psychological factors that predict latrine ownership and consistent latrine use in the rural Becho district of central Ethiopia.MethodA quantitative, cross-sectional, community based study was conducted. A total of 1047 heads of household were interviewed using a structured questionnaire. Ownership of latrine and consistent latrine use constituted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 41 publications
7
44
1
Order By: Relevance
“…The factors influencing latrine construction and use are broadly classified into demographic and socio-economic factors, knowledge and attitudes, and social influence [13,15,19,20,35,36]. Although we did not find significant differences between household size, age, marital status or literacy rates among respondents across the levels of latrine completion, other research works have reported the influence of these factors on latrine construction and use [36,37,38].…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…The factors influencing latrine construction and use are broadly classified into demographic and socio-economic factors, knowledge and attitudes, and social influence [13,15,19,20,35,36]. Although we did not find significant differences between household size, age, marital status or literacy rates among respondents across the levels of latrine completion, other research works have reported the influence of these factors on latrine construction and use [36,37,38].…”
Section: Discussioncontrasting
confidence: 70%
“…Households would more likely switch from open defecation to latrine use if latrines protect their privacy. Existing literature on CLTS indicates that convenience, comfort, and health benefits are recurring reasons for latrine use [19,20]. Similarly, a study on rural sanitation showed that privacy and safety are the major reasons for latrine construction and use among women [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations